EXPLORING STUDENTS’ ERRORS IN CONSTRUCTING SENTENCES - Andri Donal (English Study Program University of Pasir Pengaraian, 2015)
Ability to construct a good sentence is a requirement in writing an essay. However some students often found some difficulties in organizing the good sentences. They may face difficulties in various aspects, including grammar. Those difficulties faced by students are what then become mistakes or errors. The main focus of this study is to find out the types of errors in constructing sentences and the frequency of error occurrence in each type. This research is descriptive design with the sample from the second year students of English Education Program of University of Pasir Pengaraian. The data analysis was using error analysis by classifying the students‟ errors based on the surface strategy taxonomy errors involving omission, addition, misformation, and misordering. From the finding of the study, it reveals that the high frequency of error occurrence is error of omission with 40 times which means 37.7 % of error total. The next most error made by the students was in Error of misformation with 37 times or 34.9%. The students made 21 times of Error of Addition or 19.8 %. They also made 8 times of Error of misorder or 7.5 %. Based on these findings, it can be concluded that the students still have problems in constructing sentences when writing an essay.